Analisis Kualitas Air Laut Untuk Wisata Bahari di Pantai Kuangwai Desa Menceh Kecamatan Sakra Timur: ANALISIS KUALITAS AIR LAUT UNTUK WISATA BAHARI DI PANTAI KUANGWAI DESA MENCEH KECAMATAN SAKRA TIMUR - Baiq Nurussyifa' Afriani; muhammad iman, darmawan (Jurnal Teknologi Lingkungan, 2025)
Kuangwai Beach is one of the coastal areas located in Kuangwai Hamlet, Menceh Village, Sakra Timur District, East Lombok Regency, West Nusa Tenggara. As one of the tourist destinations that is currently developing, Kuangwai Beach is inseparable from the many factors that can affect its quality. This study aims to determine the quality of seawater for marine tourism at Kuangwai Beach based on Government Regulation Number 22 of 2021 concerning the Implementation of Environmental Protection and Management. This study was conducted using a purposive sampling method. Water quality measured in situ includes brightness, pH, temperature, odor, and waste. Ex situ measurements include salinity, TSS, DO, BOD5, NH3-N, and PO4-P with testing at the Marine Aquaculture Center Laboratory located in Sekotong, West Lombok. The measurement results show that the parameters of temperature, salinity, TSS, DO, and BOD5 at all stations meet the quality standards. For waste parameters, at stations 1, 2, and 3 they meet the quality standards, but at stations 4 and 5 they do not. Likewise for the pH parameter, only at station 4 it meets the standards, while stations 1, 2, 3, and 5 do not meet the quality standards. Meanwhile, for other parameters such as brightness, odor, PO4-P and NH3-N at all research stations have exceeded the threshold required in the quality standards for seawater quality for marine tourism according to Government Regulation Number 22 of 2021 concerning the Implementation of Environmental Protection and Management